Influence of Te layer on CdTe thin films and their performance on CdS/CdTe solar cells (Superficies y Vacío, 2021)
CdTe semiconductor is an absorbent material used in “tandem” photovoltaic solar cells. This material is commonly deposited by thermal evaporation presenting electrical resistivity values about of 105 W·cm to 109 W·cm. CdTe is applied in thin solar cells as p-type layer which is in contact with metal back electrode in solar cells. In the CdTe/metal junction a Schottky barrier exits; and small number of charge carriers have enough energy to get over the barrier and cross to the metal back contact. To solve part of this problem, nanostructured Te thin films were used as intermediate layers between CdTe and metal contact. Te layers whit different physical properties were deposited on CdS/CdTe structure by thermal evaporation employing different growth parameters. The electrical parameters of CdTe solar cells were influenced by p+ Te regions. p+ Te regions used as intermediate layer with large deposition time increases the FF and VOC values from 30% to 60% and 560 mV to 730 mV respectively. Also, the electrical resistivity is reduced from 106 W·cm to 103 W·cm. In this sense, Te region implemented as nanostructure allows to reduce the series resistance from 99 W to 20 W and increases the shunt resistance from 1445 W to 4424 W;  Te region as thin films demonstrated not be adequate.